Pedagogi Identitas Keagamaan: Official Knowledge dan Interkulturalisme Pendidikan Islam di Papua - Idrus al Hamid (UIN Sunan Ampel Surabaya, 2019)
This article discusses two education concepts from sociological point of view, namely official knowledge as the product of critical pedagogy experts and the concept of intercultural education that is pinned to solve the problem of identity in educational environment. This article makes Jayapura a case example where the two concepts can be implemented both theoretically and practically. With a phenomenological approach in the field, this study found that the concept of